Value Relevance of Country Governance and Economic Freedom for Foreign Portfolio Inflows in Developing and Developed Countries. - Khan, Faisal; Ullah, Hamid; Shah, Hamid; Hussain, Amir (Iqra National University, 2021)
Globalization, country governance, and economic freedom have generally led to stock market liberalization around the world. These factors are considered imperative for financial portfolio investment (FPI). This study investigates the impact of country governance and economic freedom on foreign capital inflows. For this purpose, we analyed data of 81 developed and 58 developing countries using dynamic panel regression model and system generalized method of movements (GMM). We found that governance and its components have positive and significant effects on FPI in all countries. Likewise, the index of economic freedom and its components have positive and significant effects on FPI. Moreover, in developing countries, investors are more concerned about governance than the economic freedom in the host country because the security of short term investment relies more on the state of governance and rule of law than on the assumed constant economic freedom in the short-term.